Suatu Kajian Toleransi Beragama Antar Mahasiswa Di Asrama Murung Raya Kota Palangka Raya - Muslimah, Muslimah; Eddy Lion; Eli Karliani (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
The purpose of this research is to analyze and describe religious tolerance among students at Murung Raya Dormitory, Palangka Raya City. This research uses a qualitative approach with a qualitative descriptive type. The research informants consisted of 1 head of the male dormitory manager, 1 head of the female dormitory manager, 1 administrative staff, 1 security guard, 1 Muslim student, 1 Christian and 1 Hindu and students from different sub-districts/villages 3 people. Data collection used observation, interview and documentation methods, while the data analysis technique in this study was an interactive analysis with data reduction flow, data presentation and conclusion drawing (verification). The results of the study revealed that 1) Tolerance that occurs between students is very well established. The form of tolerance that is practiced is cooperation with each other regardless of religious differences, not intimidating certain religions. Succeed in religious activities. If there are students who need help individually then other students will help regardless of religious differences. Managers also play an important role in maintaining harmony among students. One form of justice carried out by the managers is placing new students in their rooms regardless of religious differences. the administrators also make a schedule of community service, mutual cooperation, monthly meetings and hold student social gatherings. The aim is to establish familiarity, get to know each other and train cooperation between students. 2) Supporting factors The manager provides a place of worship for students and confirms the regulations that apply in the dormitory and acts as an intermediary for students. The inhibiting factor is the presence of stereotypes